PEMETAAN LANSKAP PENELITIAN AGRESIVITAS PAJAK PERUSAHAAN: PEMETAAN BIBLIOMETRIK - Mufidaturrohmah, Nur; Andriani, Sri (Jurnal Riset Akuntansi, 2024)
The self-assessment mechanism in Indonesia allows companies to independently calculate and report their tax liabilities, potentially encouraging aggressive tax practices. This study aims to identify research trends, main themes, and key factors in Corporate Tax Aggressiveness from 2014 to 2024. The method involved searching for research articles with the keyword "Tax Aggressiveness" in international journals indexed by Scopus, national journals indexed by Sinta through the Garuda website, and national journals using Publish or Perish, resulting in 400 articles. These articles were analyzed using the VOSviewer application. This research utilizes bibliometric analysis to map Corporate Tax Aggressiveness trends over the past decade. The results show a significant annual increase in publications, with VOSviewer identifying 5 clusters and 56 items related to Corporate Tax Aggressiveness research. The study concludes that academic interest in Corporate Tax Aggressiveness is growing, highlighting the importance of this topic in tax literature. The recommendation is to use the identified factors in future research on tax aggressiveness.